2015
DOI: 10.1039/c5cp03566j
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the voltage loss mechanisms in lithium–sulfur cells: the importance of electrolyte resistance and precipitation kinetics

Abstract: Understanding of the complex electrochemical, transport, and phase-change phenomena in Li-S cells requires experimental characterization in tandem with mechanistic modeling. However, existing Li-S models currently contradict some key features of experimental findings, particularly the evolution of cell resistance during discharge. We demonstrate that, by introducing a concentration-dependent electrolyte conductivity, the correct trends in voltage drop due to electrolyte resistance and activation overpotentials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 26 publications
7
71
0
Order By: Relevance
“…20 As expected, a peak in the resistance appears at all temperatures at the transition between upper and lower plateaus, associated with a maximum in electrolyte resistance, as a result of high concentrations of dissolved polysulfides in this state. 21,22 The size and location of this peak is strongly temperature dependent. In the case of discharge at 20…”
Section: Resultsmentioning
confidence: 99%
“…20 As expected, a peak in the resistance appears at all temperatures at the transition between upper and lower plateaus, associated with a maximum in electrolyte resistance, as a result of high concentrations of dissolved polysulfides in this state. 21,22 The size and location of this peak is strongly temperature dependent. In the case of discharge at 20…”
Section: Resultsmentioning
confidence: 99%
“…This decrease in capacity is mainly caused by the shortening of the lower discharge plateau, associated with the reduction to solid Li 2 S, and the increase of its overpotential (Figure 3c and Figure 3d). In recent modelling study this type of overpotential increase was attributed to differences in Li 2 S precipitation process 43 leading to: (i) a change in the electrolyte resistance due to the variation in concentration of polysulfides and Li-ions, which are formed in large quantities at high rates, (ii) the need of a larger activation overpotential with high currents to overcome the deposition of insulating Li 2 S, and subsequent decrease of available surface area, and (iii) a shift of the reduction potentials due to the consumption of the active species. In our work at discharge rates higher than 1C, the overpotential is so high that the lower-plateau reactions do not occur within the voltage window studied (Figure 3c and Figure 3d).…”
Section: Resultsmentioning
confidence: 99%
“…48 However, EIS studies carried out by Deng et al, 49 showed that the charge transfer resistance, corresponding to the activation overpotential, and the surface film resistance, are much larger than electrolyte resistance throughout the discharge event. This suggests that the cell potential can be limited by charge transfer and surface resistance even when the electrolyte conductivity is adequate.…”
Section: Methodology: Overall Construction and Governing Equationsmentioning
confidence: 99%